Relações entre hidroclimatologia, hidrodinâmica, qualidade da água e taxas de evaporação em um lago tropical urbano - Mesquita, Janine Brandão de Farias (2021)
Evaporation represents one of the main losses in surface water sources that can directly affect water availability. In this sense, the present work aimed to analyze, in an integrated way, the relationships between hydroclimatic, hydrodynamic and water quality conditions, and their impacts on the evaporation rates of an urban tropical lake, using a two-dimensional hydrodynamic model and through coupling of models. The study area is Lake Santo Anastácio, with a capacity of about 0.4 hm³ and a maximum depth of 5 m, located in the city of Fortaleza, Ceará, Brazil. This thesis was structured in two review chapters and two scientific articles. Initially, the scientific potential was identified through a literature review on hydrodynamics, water quality and evaporation. Subsequently, the two-dimensional model CE-QUAL-W2 was used to simulate the hydrodynamics and direct evaporation of the lake, and an equation for estimating evaporation based on the mass transfer method was calibrated. Direct evaporation was modeled, integrated with the analysis of the thermal characteristics of the water column, both for the condition of a stratified lake and for the hydraulic regime of complete mixing, in order to evaluate the impact of thermal stratification on evaporation rates. The modeled evaporation was compared to measurements obtained over an 11-year period (2009 to 2019) with a Class A pan. The results indicated a daily thermal stratification of up to 2 °C and an average increase of 2% in evaporation lake stratified in relation to the complete mixing regime. Comparing the modeled evaporation with that measured by the Class A pan, the average coefficients of the Class A pan (K) were between 0.66 and 0.69, below the values reported in the literature, possibly due to the high concentration of pollutants in the lake. Finally, the K coefficients were negatively correlated with wind speed (R2 of 0.51; p-value <0.05), air temperature (R2 of 0.67; p-value <0.05) and concentration of total phosphorus in the dry period (R2 of 0.41; p - value <0.05); suggesting that wind-induced phosphorus resuspension attenuated evaporation rates in the lake. The impact of different values of the K coefficients on water availability was also investigated. Finally, in the last scientific contribution, the Storm Water Management Model (SWMM) was coupled with CE-QUAL-W2 to assess the impact of hydrological characteristics on hydrodynamics, considering water quality and its impact on evaporation rates. Three years were selected, according to rainfall characteristics, from a 20-year time series: 2013 (dry), 2018 (typical) and 2019 (rainy). The hydrological simulation was carried out in SWMM and the flow time series were coupled to the CE-QUAL-W2 model. Then, two water quality models were applied: a transient complete-mix model and an empirical one, based on wind speed. Time series of total phosphorus concentrations were generated andempirical correlations between the aforementioned parameter, phosphorus loads, sanitary and hydrological variables were proposed. The modeled total phosphorus concentrations and the Biochemical Oxygen Demand (BOD) were correlated to the monthly Class A pan coefficients. There was a slight variation in hydrodynamic characteristics with an increase in annual precipitation, such as an increase in the average water temperature (comparing 2013 and 2019) and a decrease in the hydraulic residence time. These trends of increasing average water temperature and decreasing hydraulic residence time are also observed when analyzing the seasonal increase in precipitation (rainy and dry season), except for water temperature in the years 2018 and 2019. A statistically significant correlation between rainfall and hydraulic residence time was also obtained (R² of 0.79), pointing to the predominance of the influence of the inflow in the hydrodynamic patterns of the shallow lake. Furthermore, correlations were obtained between the inflow and total phosphorus (R² of 0.70); and the solid waste from sweeping and cleaning of the tributary channel and the input loads of total phosphorus (R² of 0.96 and 0.64, respectively). Finally, K coefficients were negatively correlated with total phosphorus concentrations modeled by the complete-mix model (R² of 0.76) and by the empirical model (R² of 0.52), as well as by BOD (R² of 0.85) in the dry season. Scenarios of lake level reduction due to evaporation were also analyzed. The studies pointed to the direct influence of hydroclimatic, hydrodynamic and water quality conditions on the tropical lake's evaporation rates. The results of this thesis are important to assist in the operational management of lakes and reservoirs.